2021
DOI: 10.3390/ijms23010387
|View full text |Cite
|
Sign up to set email alerts
|

B Lineage Cells in ANCA-Associated Vasculitis

Abstract: Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a systemic autoimmune disease that affects small sized blood vessels and can lead to serious complications in the lungs and kidneys. The prominent presence of ANCA autoantibodies in this disease implicates B cells in its pathogenesis, as these are the precursors of the ANCA-producing plasma cells (PCs). Further evidence supporting the potential role of B lineage cells in vasculitis are the increased B cell cytokine levels and the dysreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 154 publications
0
5
0
Order By: Relevance
“…Abnormal activation of B cells was observed in AAV patients and was associated with disease severity or poor outcomes. [ 92 , 93 , 94 ] Clinical trials have shown that depletion of B cells with rituximab is a useful treatment for AAV. [ 41 , 42 ] All evidence suggests that B cells have a vital role in the pathogenesis of AAV.…”
Section: Pathogenesismentioning
confidence: 99%
“…Abnormal activation of B cells was observed in AAV patients and was associated with disease severity or poor outcomes. [ 92 , 93 , 94 ] Clinical trials have shown that depletion of B cells with rituximab is a useful treatment for AAV. [ 41 , 42 ] All evidence suggests that B cells have a vital role in the pathogenesis of AAV.…”
Section: Pathogenesismentioning
confidence: 99%
“…They bind to neutrophils, especially in the small blood vessels. This triggers a cascade of inflammatory reactions, leading to the activation of neutrophils, which release damaging substances such as ROS and lytic enzymes and contribute to the inflammation seen in AAV [44,46,47]. Moreover, a significant contribution to tissue damage is connected with the further formation and release of neutrophil-extracellular traps (NETs) associated with neutrophil apoptosis (NETosis).…”
Section: Pathogenesis and Influence Of Neutrophilic Elements On The D...mentioning
confidence: 99%
“…ANCAs induce inflammation and endothelial damage, most notably in small‐sized blood vessels in the lungs and kidneys of the patients, eventually leading to organ dysfunction [ 22 ]. The alterations in B cell composition in patients with AAV, the prominent presence of ANCAs, and preliminary data on dysregulated intracellular signalling pathways in these cells suggest that B cells and PCs are critically involved in the pathogenesis of AAV [ 23 ].…”
Section: B Lineage Cells and Their Central Role In Autoimmune Diseasesmentioning
confidence: 99%